(untitled) (Faridpur Medical College Journal, 2011)
In 1991 WHO International Survey of Drug Utilization in Pregnancy is 86% of women took medication during pregnancy, Average of 2.9 prescriptions and despite this high rate of medication intake, most drugs are not labeled for use during pregnancy. Most women use a number of different medications during pregnancy, many of which are self-administered. It is essential to consider the following factors before prescription of drugs during pregnancy. A) Dose and duration of drug exposure is important. The larger the dose is more likely the effects. The longer the duration of drug exposure is greater chance of susceptible periods of organogenesis and developmental problem. B) Timing of exposure is very crucial. Certain organ systems may have only limited period of susceptibility for damage. C) Pathogenetic mechanism, teratogens produce their adverse effect by specific mechanism. D) Host susceptibility, variability in the genetic factors related to mechanism of certain drugs. All drugs can affects the health of the mother and fetus, therefore any drugs should be administer with care during pregnancy. Key words: Drug; pregnancy; congenital malformation; fetus DOI: 10.3329/fmcj.v5i1.6811 Faridpur Med. Coll. J. 2010;5(1):29-31